Flavonoids from the butanol extract of Carica papaya L. cultivar 'Red Lady' leaf using UPLC-ESI-Q-ToF-MS/MS analysis and evaluation of the antioxidant activities of its fractions. (October 2022) - Kumar, Sheethal S; Krishnakumar, K; John, Mathew
Highlights: Identified 11 flavonoids in C. papaya cultivar Red Lady leaf Four new flavonoid reports in papaya leaf C. papaya leaf is rich in quercetin and kaempferol glucoside derivatives Butanolic extract showed significant antioxidant activities. Abstract: Flavonoid rich foods are described as superfoods because of their potent antioxidant properties. They are natural antioxidants and have various health oriented biological benefits such as anti-inflammatory, immunomodulatory, antiviral and anticarcinogenic properties. Identification of flavonoids in the isolated butanolic extract of Carica papaya L. cultivar 'Red Lady' leaf using UPLC-Q-ToF-MS/MS is the highlight of the study. In the present study, 11 flavonoids were detected in the butanolic extract among them, luteolin, astragalin, 2-(3, 4-Dihydroxy-5-methoxyphenyl)-3, 5, 7- trihydroxy-6-metoxy-2, 3 dihydro-4H-chromen-4-one and quercetin dimer are new reports in C. papaya leaves. Flavonoids in butanolic extract were fractionated by preparative HPTLC and obtained 4 flavonoid bands. Flavonoids in each band were identified using UPLC-Q-ToF-MS. Antioxidant activity of butanolic extract and its fractions separated by preparative HPTLC were determined by FRAP assay and DPPH free radical scavenging assay. Butanolic extract showed a dose (0.05mg/ml, 0.1 mg/ml, 0.2mg/ml, 0.4mg/ml and 0.8mg/ml) dependent increment in antioxidant activity. Assay of the bands obtained by preparative HPTLC analysis showed that those containing quercetin and its glucoside derivatives have more antioxidant activity than those containing kaempferol and its glucoside derivatives. Graphical abstract: Image, graphical abstract